e-Inclusion and disabled-people-friendly web - Šimonová, Stanislava (Univerzita Pardubice, 2006)
E-inclusion represents a set of conditions for effective inclusion of all population groups in the information society. Public administration services must be user-friendly and available to all that is also to the handicapped or otherwisse disadvantaged population groups. The contribution results from te project 4530/20/FG452013 e-Government and the specific target population groups.
Keywords: E-Government; webové stránky; uživatelská příjemnost; hendikepovaní uživatelé